Programming Bioactive Architectures with Cyclic Peptide Amphiphiles. Issue 8 (14th July 2015) - Kuan, Seah Ling; Wang, Tao; Raabe, Marco; Liu, Weina; Lamla, Markus; Weil, Tanja
Abstract: We present a versatile approach for the synthesis of cyclic peptide amphiphiles of the hormone somatostatin (SST) with tunable lipophilic tails to program bioactive nanoarchitectures. A novel bis‐alkylation reagent is synthesized that facilitates the functionalization of SST with a thiol anchor. Different hydrophobic moieties are introduced inspired by a biomimetic palmitoylation approach which opens access to cyclic peptide amphiphiles that display rich self‐organization and cell membrane interactions. Abstract : Made to order : Cyclic peptide amphiphiles prepared by a bioinspired approach are employed to program various bioactive nanoarchitectures that display rich self‐organization and cell membrane interactions.